2017
DOI: 10.1177/0149206317733511
|View full text |Cite
|
Sign up to set email alerts
|

Upsides to Dark and Downsides to Bright Personality: A Multidomain Review and Future Research Agenda

Abstract: It has become common practice to refer to personality traits as being either bright or dark, and a wealth of research has provided support for the effects of both bright traits and dark traits in organizations. This research has largely focused on explaining the downside of dark traits and the upside of bright traits. However, a recent trend has emerged in which scholars are challenging the long-standing convention that bright traits are always beneficial and dark traits are always detrimental. Instead, novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
159
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(182 citation statements)
references
References 185 publications
(250 reference statements)
15
159
1
Order By: Relevance
“…For example, our study relied on a global measure of conscientiousness, though post hoc tests suggested that examining lower order dimensions of conscientiousness may shed additional light on the main relationships. To this end, we echo others in noting that trait measures designed to capture narrower subfacets may provide meaningful clarity (e.g., Roberts et al, 2005;Smith et al, 2018). We likewise note that our study found a complex relationship between leader conscientiousness and followers' shared satisfaction with the leader (i.e., a team-level construct).…”
Section: Limitations and Future Directionssupporting
confidence: 81%
See 1 more Smart Citation
“…For example, our study relied on a global measure of conscientiousness, though post hoc tests suggested that examining lower order dimensions of conscientiousness may shed additional light on the main relationships. To this end, we echo others in noting that trait measures designed to capture narrower subfacets may provide meaningful clarity (e.g., Roberts et al, 2005;Smith et al, 2018). We likewise note that our study found a complex relationship between leader conscientiousness and followers' shared satisfaction with the leader (i.e., a team-level construct).…”
Section: Limitations and Future Directionssupporting
confidence: 81%
“…Heeding calls in related research (Hough, 1992;Roberts, Chernyshenko, Stark, & Goldberg, 2005;Smith, Hill, Wallace, Recendes, & Judge, 2018), we conducted supplementary analyses to explore whether examining leader conscientiousness at the subfacet level might further inform our model. 4 Although our hypotheses did not specify first-order dimensions of conscientiousness, our arguments did imply that leader role authenticity acts as a hedge against conscientious leaders' tendencies to pursue order, which then affects their adaptability.…”
Section: Supplementary Post Hoc Analysesmentioning
confidence: 99%
“…When honesty‐humility is reversed, it is almost synonymous with measures of the Dark Triad (Aghababaei, Mohammadtabar, & Saffarinia, ; Lee & Ashton, ). Thus, the inclusion of honesty‐humility aligns with recent interest in dark personality (Smith, Hill, Wallace, Recendes, & Judge, ). The HEXACO model may also be particularly useful in employee selection settings (Anglim, Morse, De Vries, MacCann, & Marty, ; Hough & Connelly, ) where organisations seek to identify job applicants who are more likely to engage in bullying, theft, and other counterproductive work behaviours.…”
Section: An Alternative Taxonomy: the Hexacomentioning
confidence: 57%
“…Personality research has been emerged as a backbone in main stream OB research. Investigation of traits are becoming way complex than it was investigated previously (Smith, Hill, Wallace, Recendes, & Judge, 2018). Nowadays, the theoretical perspectives focus on investigating the deceptive, manipulative and opportunistic traits such as Machiavellianism (Carter, Guan, Maples, Williamson, & Miller, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is not recommended by the researchers to investigate the linear personality-outcome relationships because of their complexities. Hence, there is a need to figure out the person's intents and the underlying interventions for investigating personality associations (Smith, Hill, Wallace, Recendes, & Judge, 2018).…”
Section: Introductionmentioning
confidence: 99%